Photodegradation and in‐Situ SERS Monitoring Properties of Ag@AgCl Anchored on Sea Urchin‐shaped Fe3O4@C/1D PANI Nanoparticles. Issue 9 (1st March 2022) - Chen, Qingtao; Liang, Weiwei; Shi, Xiangdong; Yang, Maosen; Qin, Xiaoyun; Jiang, Liying; Jia, Chunxiao; Chen, Fenghua; Luo, Dan
Abstract: Here, sea urchin‐shaped nanoparticles were first fabricated by growing one dimensional polyaniline (1D PANI) nanowire array on carbon layer encapsulated Fe3 O4 nanoparticles, and then Ag@AgCl photocatalyst were tightly anchored on the surface of PANI nanowire to form Fe3 O4 @C/1D PANI/Ag@AgCl bifunctional material as recyclable adsorption‐photocatalysts and surface enhanced Raman scattering (SERS) substrate to monitor photocatalytic degradation of dye molecules. Compared with Fe3 O4 @C/1D PANI, Ag@AgCl and Fe3 O4 @C/PANI/Ag@AgCl catalysts, the fast electron transfer characteristics of conductive 1D PANI nanowire array and the synergistic effect between the surface plasmon resonance of Ag and the photosensitive characteristic of AgCl, enabled the prepared Fe3 O4 @C/1D PANI/Ag@AgCl excellent adsorption‐photocatalytic efficiency for the degradation of RhB under visible‐light irradiation. PL spectra and a series of photoelectrochemical measurements were carried out to investigate the reasons for such enhanced photocatalytic activity and the possible improved photocatalytic degradation mechanism was proposed. Meanwhile, the detection of the presence of RhB and its degradation process were achieved with real‐time SERS technology employing the prepared Fe3 O4 @C/1D PANI/Ag@AgCl photocatalyst itself as the substrate. All the results made it great promise for simultaneously monitoring and removal of organic contaminants in water. Abstract : Bifunctional material prepared by anchoring Ag@AgCl photocatalysts onto the 1D PANI nanowire array on the surface of sea urchin‐shaped Fe3 O4 @C/1D PANI were designed for enhanced adsorption‐visible light photocatalytic degradation and simultaneously in‐situ surface enhanced Raman scattering (SERS) monitoring of organic pollutants.